PSYCHOLOGICAL EMPOWERMENT AND WORK ENGAGEMENT AMONG EDUCATORS: THE MEDIATING ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT IN PROMOTING INFORMATION LITERACY CULTURE - Asshidiq, Hasby; Hasanuddin, Hasanuddin; Hardjo, Suryani (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
In the context of law enforcement education, sustaining the engagement of educators is essential for institutional transformation and the cultivation of information literacy culture. This study investigates the influence of psychological empowerment on work engagement among educators (GADIK) at Sekolah Polisi Negara (SPN) Hinai, with perceived organizational support (POS) as a mediating variable. Using a quantitative method, data were collected from 177 educators through total sampling and analyzed using Structural Equation Modeling (SEM). The findings reveal that psychological empowerment significantly influences POS (β = 0.337) and work engagement (β = 0.256). Additionally, POS demonstrates a significant mediating effect in the relationship between psychological empowerment and work engagement, as confirmed by the Sobel test (Z = 2.148; p < 0.05). The dimensions of “meaning” and “competence” emerged as the strongest contributors to empowerment, while “organizational rewards” and “working conditions” were the most influential indicators of POS. These results affirm that a supportive organizational climate amplifies the effect of empowerment on engagement and highlight the importance of aligning individual psychological resources with systemic support mechanisms. Theoretically, the findings are grounded in Social Exchange Theory, and practically, they underscore the need for integrated leadership strategies that foster both autonomy and recognition. This study contributes to the development of a holistic framework for enhancing educator engagement within police education settings, ultimately strengthening the institution’s capacity to produce ethically grounded and information-literate law enforcement officers.